Identification of a novel orally bioavailable NLRP3 inflammasome inhibitor. Issue 21 (1st November 2020) - Agarwal, Sameer; Pethani, Jignesh P.; Shah, Hardik A.; Vyas, Vismit; Sasane, Santosh; Bhavsar, Harsh; Bandyopadhyay, Debdutta; Giri, Poonam; Viswanathan, Kasinath; Jain, Mukul R.; Sharma, Rajiv
Graphical abstract: Abstract: NLRP3 inflammasome mediated release of interleukin-1β (IL-1β) has been implicated in various diseases, including COVID-19. In this study, rationally designed alkenyl sulfonylurea derivatives were identified as novel, potent and orally bioavailable NLRP3 inhibitors. Compound 7 was found to be potent (IL-1β IC50 = 35 nM; IL-18 IC50 = 33 nM) and selective NLRP3 inflammasome inhibitor with excellent pharmacokinetic profile having oral bioavailability of 99% in mice.